La Biennale die Venezia : participating countries, collateral events. - Biennale Venetië 2005; Abadzieva, Sonja; Arestizabal, Irma; Arrhenius, Sara; Babias, Marius; Bailey, Jann L.M.; Baldi, Pio; Banz, Stefan; Bikse, Aigars; Bonito Oliva, Achille; Boonma, Montien; Bowman, Jason, E.; et al. (Venezia : La Biennale di Venezia, 2005)
Abdul, Lida ; Abgarian, Sona ; Aghasyan, Vahram ; Ahunov, Vyacheslav ; Airo, Mario ; Almeida, Helena ; Altay, Can ; An Architektur ; Andrè, Patrick ; anothermountainman ; Antich, Carolina ; Atabekov, Said ; Atelier van Lieshout ; Babak, Mykola ; Bäckström, Miriam ; Bae Young-Whan ; Bahc, Yiso ; Baktruppen ; Ban, Shigeru ; Bartolini, Massimo ; Basov, Izrail ; Bedoya, Luz Maria ; Bejenaru, Matei ; Bellamine, Fouad ; Belmore, Rebecca ; Ben-Ner, Guy ; Beninati, Manfredi ; Bennani Moha, Mohamed ; Bloomer, Patrick ; Boonma, Montien ; Boronilov, Maxim ; Boyadjiev, Luchezar ; Brandes, Stephen ; Branislav, Petric ; Brunner-Szabo, Eva ; Bunga, Carlos ; Burdelez, Pasko ; Campement Urbain ; Cantor, Mircea ; Cecchini, Loris ; Chalayan, Hussein ; Chan Yuk Keung ; Charlesworth, Ian ; Conlon, Donna ; Cortadellas, Montserrat ; Court, John ; Crasset, Matali ; d'O, Honoré ; Dan, Calin ; Dautovic, Stanisa ; Denis, Maxence ; Diaz, Gonzalo ; Diaz, Polibio ; Djoumaliev, Muratbek ; Dodiya, Atul ; Dube, Anita ; Echavarria, Juan Manuel ; Eriksson, Annika ; Ersen, Esra ; et. al ; Factotum ; Faldbakken, Matias ; Favaretto, Lara ; Fayyazi Azad, Bita ; Ferro, Chelpa ; Filko, Stano ; Finnemore, Peter ; Fiskin, Vadim ; Floricic, Alen ; Ford, Laura ; Foucault, Henri ; Franzella, Daniele ; Fridriksdóttir, Gabriela ; Garry, Mark ; Gelatin ; Gilbert & George ; Gimhongsok ; Giuliani, Giuliano ; González Palma, Luis ; Gonzalez, Monica ; Gordon, Douglas ; Granjon, Paul ; Grigorescu, Ion ; Group F5 ; Hadjimichalis, George ; Hakobian, Diana ; Hammad, Salah El Din Ahmed Mohamed ; Harahan, Seamus ; van Heeswijk, Jeanne ; Heikkilä, Jaakko ; Hiromi, Masuda ; Ho Chang Yung ; Hogg, Michael ; Höller, Carsten ; Hukkataival, Helinä ; Ibrahim, Noor ; Iorio, Silvia ; Ishiuchi, Miyako ; Jeong-Hwa, Choi ; etc.
Biennale di Venezia, Venetië, 2005-06-12 tot 2005-11-06
boek